(untitled) (Journal on Excellence in College Teaching, 2024)
Reusable, or non-disposable, assignments are becoming increasingly popular with the proliferation of Open Education Practices. However, no clear nomenclature and taxonomy for these assignments exists in the literature. This literature review explores the various names and conceptualizations under which non-disposable assignments are discussed. Building upon the definition and three-part framework proposed by Seraphin et al. (2019), the authors propose an additional typology and sub-designations of the various types of reusable assignments that can provide value beyond a single point-in-time evaluation of learning.